Paleogene Sedimentary Records of the Paleo‐Jinshajiang (Upper Yangtze) in the Jianchuan Basin, Yunnan, SW China - Mengying He; Hongbo Zheng; Peter D. Clift; Zixuan Bian; Qing Yang; Bihui Zhang; Lei Xia (Geochemistry, Geophysics, Geosystems, 2021)
Abstract Cenozoic surface uplift of Tibetan Plateau has driven the birth and reorganization of large river systems in Asia. The development of the Yangtze River, closely linked to plateau uplift, has important implications for the regional tectonic‐geomorphology processes, but is still under debate. The key scientific question is whether the Upper Yangtze (upper Jinshajiang) once flowed southeast to the South China Sea. In this study, we carried out provenance analysis on Paleogene sedimentary rocks in the Jianchuan Basin, composed of the Baoxiangsi, Jinsichang, and Shuanghe formations. We compared them with similar deposits in other regional basins, as well as with potential sources. Heavy‐mineral and geochemical data show that sediments from the Jinsichang formation are more mature compared with those from the Shuanghe and Baoxiangsi formations. The Jinsichang formation represents the products of a large fluvial system, whereas the Baoxiangsi formation is mainly dominated by local sources. The Shuanghe formation contains material from both distant sources and locally eroded materials. Detrital zircon U‐Pb age patterns from the Jianchuan Basin are similar to those in sediments in the Gonjo, Simao, and Chuxiong basins, and show great similarity with the modern Jinshajiang River. Statistical analysis of the zircon ages suggests that the Songpan‐Ganzi terrane was the primary source for all sediments, while the Yangtze Craton and northern Qiangtang terrane constitute secondary sources. Taken together these data confirm that a paleo‐Jinshajiang flowed south toward to the South China Sea from the SE Tibetan Plateau in the late Eocene, constraining the age of formation of the First Bend.